Turkish Public Supports Role In Kosovo Action. - United States Information Agency. Office of Research and Media Reaction.; Fleury, Christopher J. (Tufts University. Tisch Library., 2019)
This just-completed USIA survey in Turkey finds that the Turkish public is solidly behind the NATO action in the Federal Republic of Yugoslavia (FRY), evidently seeing the allied campaign as a chance for Turkey to assume a leadership role within the international community.; European Opinion Alert L-45-99